Evaluation of magnetic & humidity-dielectric response of tungsten substituted Y-type barium hexaferrite (Ba2Co2WxFe12−xO22, 0.0 ≤ x ≤ 2.0) synthesized by solid-state reaction route - Suthar M.; Roy P.K. (My University, 2025)
In this work, the effect of tungsten substituted Y-type barium hexaferrite has been studied for its magnetic and humidity-dependent dielectric properties, which facilitates the materials selection criteria for any specific range of applications within variable atmospheric parameters. The pristine and tungsten substituted Y-type hexaferrites (Co2-Y) having a general formula of Ba2Co2WxFe12-xO22 (x = 0.0, 0.5, 1.0, 1.5, 2.0) have been synthesized by solid-state reaction method. The as-prepared calcined hexaferrite powders are analyzed for their crystalline phase analysis, structural bondings, optical properties, microstructural features, and magnetic characteristics. The frequency-dependent humidity-dielectric response has been analyzed using an impedance analyzer for a wide range of frequencies (20 Hz to 10 MHz) & relative humidity variation from 20 to 95%. The result suggests a continuously decreasing behavior of resistivity and a reverse trend in dielectric response with increasing relative humidity (RH). The superiority of these hexaferrite samples is analyzed by calculating the humidity sensitivity factor. The Ba2Co2W1Fe11O22 hexaferrite shows its superiority in terms of humidity sensing factor (higher sensitivity towards moisture, responsible for quick responses to minor RH variations), which may explain the suitability of this material to be utilized within the development of a humidity sensor operable at higher frequencies & low operating voltage along with enriched environmental steadiness. © 2023 Elsevier B.V.